Heritage Art with an Intent. Issue 2 (December 2020) - Sabnani, Nina; Buser, Michael
A collaborative research project called JAL explored the role and potential for the arts to support water security activities in Rajasthan. The intent was to learn about some of the challenges facing people in rural Rajasthan and to draw on the region's heritage toward arts-led research, practice and thinking to help address critical water issues. One project that emerged from the fieldwork took its inspiration from the murals of Shekhawati and the ancient phad (painted scroll with stories) storytelling tradition of Rajasthan. It involved local artists who painted a wall with water stories in the village Jhakhoda. The artists also painted a scroll that a local storyteller could use to share with other villages. This article offers a report of the mural project, its process and outcome and the insights gained from a close engagement with the community in the village. The experiences signal the rich potential of collaboration with communities and across disciplines, as well as the role of the arts and artists in engaging with and addressing critical global challenges, such as water security.